Biovalorization of Friedelane Triterpenes Derived from Cork Processing Industry Byproducts - Moiteiro, Cristina; Marcelo Curto, Maria João; Mohamed, Nagla; Bailén, María; Martínez-Díaz, Rafael; González-Coloma, Azucena (Journal of Agricultural and Food Chemistry, 2006)
Here, we describe the synthesis, bioactivity screening, and structure?activity relationships of various synthetic triterpenoids prepared from the cork processing byproducts friedelin (1) and 3-hydroxyfriedel-3-en-2-one (2) via oxidative procedures. The synthesis of compounds 2α-trimethylsiloxyfriedelan-3-one (17), friedelin-2,3-lactone (18), friedelin-3-oxime (19), and friedelin-3,4-lactam (20) is also described. We have studied the insecticidal and phytotoxic potential of these compounds, their selective cytotoxic effects on insect and mammalian cells, and their antiparasitic effects. Structural modifications of the A-ring of friedelin (1) improved its insecticidal activity with derivatives 5, 2,3-secofriedelan-2-al-3-oic acid (6), its acetylated derivative 6a, 3?- and 3α-hydroxyfriedelane (9 and 10), 3α-hydroxyfriedel-2-one (11), 4?-hydroxyfriedel-3-one (16), the acetylated 10a, 3,4-secofriedelan-4-oxo-3-oic-acid (14), lactone 18, and the oxime 19 being stronger insecticides than the parent compound. Methyl-3-nor-2,4-secofriedelan-4-oxo-2-oic acid (12) and its acetylated derivative 12a also showed insecticidal activity in contrast to their inactive parent compound 2. The postingestive effects and cytotoxicity of these compounds suggest a multifaceted insecticidal mode of action. These structural modifications did not result in better phytotoxic agents than the parent compounds except for lactam 20 and yielded several moderately active antiparasite derivatives (seco acids 6, 12, 14, and 4? -hydroxyfriedel-3-one 16) with cytotoxic effects on mammalian cells. Keywords: Quercus suber; cork smoker wash solids; triterpene friedelanes; Spodoptera littoralis; Lactuca sativa; Trypanosoma cruzi; Leishmania infantum; antifeedant; phytotoxic; antiparasitic
doi: 10.1021/jf0531151doi: 10.1021/jf0531151The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: antifeedant; antiparasitic; cork smoker wash solids; Lactuca sativa; Leishmania infantum; phytotoxic; Quercus suber; Spodoptera littoralis; triterpene friedelanes; Trypanosoma cruzi

Biovalorization of Friedelane Triterpenes Derived from Cork Processing Industry Byproducts (Journal of Agricultural and Food Chemistry, 2006)
Here, we describe the synthesis, bioactivity screening, and structure?activity relationships of various synthetic triterpenoids prepared from the cork processing byproducts friedelin (1) and 3-hydroxyfriedel-3-en-2-one (2) via oxidative procedures. The synthesis of compounds 2α-trimethylsiloxyfriedelan-3-one (17), friedelin-2,3-lactone (18), friedelin-3-oxime (19), and friedelin-3,4-lactam (20) is also described. We have studied the insecticidal and phytotoxic potential of these compounds, their selective cytotoxic effects on insect and mammalian cells, and their antiparasitic effects. Structural modifications of the A-ring of friedelin (1) improved its insecticidal activity with derivatives 5, 2,3-secofriedelan-2-al-3-oic acid (6), its acetylated derivative 6a, 3?- and 3α-hydroxyfriedelane (9 and 10), 3α-hydroxyfriedel-2-one (11), 4?-hydroxyfriedel-3-one (16), the acetylated 10a, 3,4-secofriedelan-4-oxo-3-oic-acid (14), lactone 18, and the oxime 19 being stronger insecticides than the parent compound. Methyl-3-nor-2,4-secofriedelan-4-oxo-2-oic acid (12) and its acetylated derivative 12a also showed insecticidal activity in contrast to their inactive parent compound 2. The postingestive effects and cytotoxicity of these compounds suggest a multifaceted insecticidal mode of action. These structural modifications did not result in better phytotoxic agents than the parent compounds except for lactam 20 and yielded several moderately active antiparasite derivatives (seco acids 6, 12, 14, and 4? -hydroxyfriedel-3-one 16) with cytotoxic effects on mammalian cells. Keywords: Quercus suber; cork smoker wash solids; triterpene friedelanes; Spodoptera littoralis; Lactuca sativa; Trypanosoma cruzi; Leishmania infantum; antifeedant; phytotoxic; antiparasitic
doi: 10.1021/jf0531151

Cork (Ullmann's Encyclopedia of Industrial Chemistry, 2000)
The article contains sections titled: 1.Introduction1.1.Definition and Origin1.2.History1.3.Morphology1.3.1.Microscopic Aspects1.3.2.Macroscopic Aspects1.4.Chemical Composition1.4.1.Suberin1.4.2.Lignin1.4.3.Polysaccharides1.4.4.Waxes1.4.5.Tannins1.4.6.Other Components1.5.Physical and Mechanical Properties2.Cork Extraction3.Production of Cork Based Products3.1.Disks and Cork Stoppers3.2.Granulates and Broken3.3.Composition Cork3.3.1.Floor and Wall Coverings3.3.2.Agglomerated Disks and Cork Stoppers3.3.3.Corkrubber3.4.Insulation Corkboard3.5.Other Specific Products4.Uses4.1.Stoppers4.2.Civil Construction4.3.Industrial Applications4.4.Automotive Industry4.5.Other Specific Uses5.Quality and Standardization5.1.Standardization and Testing5.2.Quality in Cork Production6.Economic Aspects6.1.Forestall Production6.2.Personnel and Companies6.3.Consumption of Products and Markets6.4.Producers7.Environmental and Toxicological Aspects7.1.Industrial Wastes7.2.Recycling and Treatments7.3.Emissions8.Legal Aspects

Cork - Gil, Luis; Moiteiro, Cristina (Ullmann's Encyclopedia of Industrial Chemistry, 2000)
The article contains sections titled: 1.Introduction1.1.Definition and Origin1.2.History1.3.Morphology1.3.1.Microscopic Aspects1.3.2.Macroscopic Aspects1.4.Chemical Composition1.4.1.Suberin1.4.2.Lignin1.4.3.Polysaccharides1.4.4.Waxes1.4.5.Tannins1.4.6.Other Components1.5.Physical and Mechanical Properties2.Cork Extraction3.Production of Cork Based Products3.1.Disks and Cork Stoppers3.2.Granulates and Broken3.3.Composition Cork3.3.1.Floor and Wall Coverings3.3.2.Agglomerated Disks and Cork Stoppers3.3.3.Corkrubber3.4.Insulation Corkboard3.5.Other Specific Products4.Uses4.1.Stoppers4.2.Civil Construction4.3.Industrial Applications4.4.Automotive Industry4.5.Other Specific Uses5.Quality and Standardization5.1.Standardization and Testing5.2.Quality in Cork Production6.Economic Aspects6.1.Forestall Production6.2.Personnel and Companies6.3.Consumption of Products and Markets6.4.Producers7.Environmental and Toxicological Aspects7.1.Industrial Wastes7.2.Recycling and Treatments7.3.Emissions8.Legal Aspects
The following values have no corresponding Zotero field: periodical: Ullmann's Encyclopedia of Industrial Chemistry electronic-resource-num: 10.1002/14356007.f07_f01
Keywords: composition (voyant); Cork; insulation; products; stoppers